Integrasi Local Wisdom dalam Mereduksi Inclusion-Exclusion Error Pendistribusian Zakat: Studi Kolaborasi BAZNAS dan UPZ Masjid di Bojonegoro - Amilatul Hidayati; Airlangga Bramayudha (Journal of Islamic Economics Studies and Practices, 2026)
Zakat distribution in Indonesia still faces serious targeting challenges, particularly related to the gap between the number of eligible recipients (mustahik) and the distribution capacity of official zakat institutions. This study aims to analyze how local wisdom can be integrated through collaboration between the Bojonegoro Regency BAZNAS (National Zakat Agency) and the Mosque Zakat Collection Unit (UPZ) to strengthen the accuracy of zakat distribution and identify potential structural inclusion and exclusion errors. This study uses a descriptive qualitative approach, with data collected through in-depth interviews with BAZNAS Bojonegoro staff in the collection and distribution sector, direct observation, and documentation studies. The study shows that BAZNAS Bojonegoro has implemented a well-planned distribution error prevention system through the Annual Work Plan and Budget and multi-layered assessments before distribution. Mustahik who have not received zakat within a certain period are not excluded errors, but follow the planned RKAT allocation sequence. The Mosque UPZ acts as a supporter of BAZNAS, which is required to report all its programs and finances to BAZNAS. It also functions as a community communication bridge that reduces the difference in expectations between BAZNAS's formal mechanisms and the views of mustahik. The mechanism for renewing the UPZ decree every five years, accompanied by a re-eligibility test, has proven effective in rigorously maintaining the quality of the mosque UPZ ecosystem. This research contributes to a hybrid zakat distribution model that combines formal BAZNAS planning with the intelligence of the local mosque UPZ. Pendistribusian zakat di Indonesia masih menghadapi tantangan serius dalam penargetan, terutama terkait dengan kesenjangan antara jumlah mustahik yang berhak dan kapasitas distribusi lembaga zakat resmi. Penelitian ini bertujuan untuk menganalisis cara integrasi kearifan lokal melalui kolaborasi antara BAZNAS Kabupaten Bojonegoro dan Unit Pengumpul Zakat Masjid dalam memperkuat akurasi distribusi zakat, serta mengidentifikasi potensi kesalahan inklusi dan eksklusi yang bersifat struktural. Penelitian ini menggunakan pendekatan kualitatif deskriptif, dengan pengumpulan data melalui wawancara mendalam terhadap staf BAZNAS Bojonegoro di sektor pengumpulan dan pendistribusian, observasi langsung, serta studi dokumentasi. Penelitian menunjukkan bahwa BAZNAS Bojonegoro telah menerapkan sistem pencegahan kesalahan distribusi yang terencana dengan baik melalui Rencana Kerja dan Anggaran Tahunan serta penilaian berlapis sebelum distribusi. Mustahik yang belum mendapatkan zakat dalam periode tertentu bukanlah kesalahan eksklusi, tetapi mengikuti urutan alokasi RKAT yang telah direncanakan. UPZ Masjid berperan sebagai pendukung BAZNAS yang wajib melaporkan seluruh program dan keuangannya kepada BAZNAS, serta berfungsi sebagai jembatan komunikasi komunitas yang mengurangi perbedaan harapan antara mekanisme formal BAZNAS dan pandangan mustahik. Mekanisme pembaruan SK UPZ setiap lima tahun dengan uji kelayakan ulang terbukti efektif dalam menjaga kualitas ekosistem UPZ Masjid secara ketat. Penelitian ini memberikan kontribusi pada model distribusi zakat hibrid yang menggabungkan perencanaan formal BAZNAS dengan kecerdasan komunitas lokal UPZ Masjid